Phase Manipulating toward Molybdenum Disulfide for Optimizing Electromagnetic Wave Absorbing in Gigahertz. (2nd March 2021) - Ning, Mingqiang; Jiang, Peiheng; Ding, Wei; Zhu, Xuebin; Tan, Guoguo; Man, Qikui; Li, Jingbo; Li, Run‐Wei
Abstract: Molybdenum disulfide (MoS2 ) has been proved to be a potential electromagnetic wave (EMW) absorber. However, the limited EMW attenuation mechanisms and conductivity have always been recognized as the major challenges impeding their further developments. In this study, a new dielectric tuning strategy giving rise to high EMW attenuation performance by manipulating phase content (with 0, 24, 50, and 100 wt% 1T phase) toward MoS2 is demonstrated. The greatly introduced 2H/1T interfaces facilitate the dipole distribution dynamics, and the metal‐semiconductor mixed phase enhances the electron transfer ability. Benefiting from the structural merits, the MoS2 with 50 wt% 1T absorber delivers the maximum reflection loss of −45.5 dB and effective absorbing bandwidth of ≈3.89 GHz, corresponding to nearly ten times higher than that of pure 2H counterpart. Moreover, the Computer Simulation Technology (CST) simulation and Lorentz transmission electron microscope are performed to visualize the structural advantages of MoS2 absorbers with mixed 2H/1T phases. By manipulating the phase compositions, this study provides a deep understanding and opens an avenue in developing efficient and high performance transition metal dichalcogenides (e.g., WS2, MoSe2, and WSe2 ) absorbers. Abstract : A new phase manipulating strategy giving rise to high electromagnetic wave (EMW) attenuation toward MoS2 is demonstrated. The rationally introduced 2H/1T phase interfaces optimize the input impedance characteristics and boost the inhomogeneous charge distribution, thereby presenting the enhanced EMW absorbing abilities. This study inspires a general approach toward tuning the EMW absorbing abilities of transition metal dichalcogenides for practical applications.